Differential insulin response characteristics of graphene oxide–gold nanoparticle composites under varied synthesis conditions - Qian Zhang; Yanjun Pan; Jin Pan; Zhichen Wang; Ruyi Lu; Jing Sun; Jingyi Feng (PLoS ONE, 2025)
The structural alterations in the constituent materials of nanocomposites such as graphene nanocomposites typically induce changes in their properties including mechanical, electrical, and optical properties. Therefore, by altering the preparation conditions of nanocomposites and investigating their responsiveness to basic biomolecules (such as proteins), it is possible to explore the application potentials of the composites and guide development of new nanocomposite preparation. In this study, different composites of graphene oxide and gold nanoparticles (AuNPs/GO) were obtained by varying the volumes of reducing agents used in the one-pot hydrothermal method. Insulin was chosen as a basic protein to study the response characteristics of AuNPs/GO under different preparation conditions. Optical responses of these composites to pure insulin and various commercial insulin types were all explored for the first time. The results indicated that AuNPs/GO could optically respond to insulin, including pure insulin and various types of commercial insulin, and changes in the preparation conditions could really influence this response. Moreover, optimal preparation conditions could be determined by an optical method for the largest responses of the nanocomposites to insulin. Based on previous research and the results of this study, it is speculated that the responses of AuNPs/GO to insulin may attribute to glutamic acids, asparagines, and glutamines on insulin, which may interact with AuNPs/GO, particularly with the AuNPs in the composites. Besides, the AuNPs/GO could exhibit relatively stable responses to various commercial insulin types and detect the concentration of specific branded commercial insulin with smaller errors. In summary, this study demonstrated the application potential of AuNPs/GO in areas such as drug testing and production, while also furnishing an experimental foundation and direction for further applications of AuNPs/GO in biosensing and biomolecule detection.